Dosage Evaluation and Antioxidant Activity Test of Lotion of Ethanol Extract of Belimbing Wuluh Leaf (Averrhoa Bilimbi L.) - Ernoviya Ernoviya; Afriadi Afriadi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
This study aims to make and evaluate the lotion formula from ethanol extract of star fruit leaves (Averrhoa bilimbi L.) and test the antioxidant activity of the lotion. The research method used is experimental, making lotions and testing antioxidant activity from July to October 2023 at the Semi-Solid Preparation Technology Laboratory, Department of Pharmacy, Poltekkes Kemenkes Medan, and Research Laboratory, University of North Sumatra. In the preparation stage, star fruit leaf simplisia was extracted by maceration using a 95% ethanol solvent. The lotion formula was made with ingredients such as PEG 4000, stearyl alcohol, glycerin, sodium lauryl sulfate, coconut oil, nipagin, and distillate water, with varying concentrations of ethanol extract of star fruit leaves. The formulation was evaluated through organoleptic, homogeneity, pH, spreadability, and viscosity tests. The results showed that the lotion produced had a homogeneous shape and aroma to the concentration of ethanol extract. In addition, the pH of the lotion is also within the safe range for human skin. The spreadability test showed the lotion's ability to spread on the skin, which met the requirements for lotions with spreadability values between 5 and 7 cm. The viscosity of the lotion was also by the set standards. Stability tests were conducted to monitor the physical and chemical changes of the lotion over four weeks. The results showed that lotions with 1% and 3% ethanol extract concentrations were stable during the study period. However, the 5% concentration experienced inhomogeneity changes in the third week. In conclusion, lotion with ethanol extract of star fruit leaves at 1% and 3% concentration can produce a good and stable formula. However, the antioxidant activity of the lotion is still in the weak to moderate category. This research contributes to developing plant-based natural cosmetic products for skin care. Keywords: Antioxidant Activity, Belimbing Wuluh, Ethanol Extract, Evaluation, Lotion